Ternary precursor and preparation method thereof, positive electrode material and preparation process thereof, and battery

The ternary precursor is prepared through the design of gradient nickel content of the core, transition layer and shell and the co-precipitation method, which solves the problems of insufficient capacity, thermal stability and interface stability of the ternary positive electrode material, and achieves high capacity and excellent cyclic stability.

CN120535036APending Publication Date: 2025-08-26JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202510716757.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing ternary cathode materials have problems such as insufficient capacity, insufficient thermal stability and insufficient interface stability.

Method used

The structural design of the core, transition layer and shell is adopted. The core has the highest nickel content and the shell has the lowest nickel content. The transition layer serves as a buffer layer. The nickel content gradient changes, combined with magnesium doping, optimizes the particle size and thickness, and prepares the ternary precursor by co-precipitation method.

Benefits of technology

The capacity and cyclic stability of the ternary precursor and the prepared positive electrode material at room temperature and high temperature are improved, the thermal stability and structural stability are enhanced, and the interface side reaction is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005428434910000161
    Figure BDA0005428434910000161
  • Figure BDA0005428434910000162
    Figure BDA0005428434910000162
  • Figure BDA0005428434910000171
    Figure BDA0005428434910000171
Patent Text Reader

Abstract

The invention provides a ternary precursor and a preparation method thereof, a positive electrode material and a preparation process thereof, and a battery. The ternary precursor comprises an inner core, and a transition layer and a shell which are sequentially coated outside the inner core, the nickel content of the inner core is gt; the nickel content of the transition layer is gt; and the nickel content of the shell. The inner core in the ternary precursor has the highest nickel content, so that the capacity of the positive electrode material prepared from the ternary precursor is ensured; the nickel contents of the inner core, the transition layer and the shell are changed in a gradient manner, so that the thermal stability of the ternary precursor is improved; the shell reduces the interface side reaction between the positive electrode material prepared from the ternary precursor and an electrolyte; the transition layer can be used as a buffer layer between the inner core and the shell, so that the ternary precursor and the structural stability are improved. Therefore, the battery containing the positive electrode material prepared from the ternary precursor has excellent capacity and cycling stability at normal temperature and high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries and relates to a ternary precursor, and in particular to a ternary precursor and a preparation method thereof, a positive electrode material and a preparation process thereof, and a battery. Background Art

[0002] Lithium-ion batteries, as highly efficient and environmentally friendly energy storage devices, have been extensively researched and applied over the past few decades. With the growing demand for portable electronics, electric vehicles, and large-scale energy storage systems, the performance requirements for lithium-ion batteries are also increasing. As a key component of lithium-ion batteries, the performance of cathode materials directly affects the battery's energy density, cycle life, safety, and cost.

[0003] Traditional lithium-ion battery cathode materials, such as lithium cobalt oxide (LiCoO2) and lithium manganese oxide (LiMn2O4), although excellent in some aspects, have certain limitations in terms of energy density, cost and safety. To overcome these limitations, researchers have begun to explore new cathode material systems, among which ternary cathode materials have attracted much attention due to their high energy density, good cycle stability and low cost.

[0004] However, despite the obvious performance advantages of ternary cathode materials, they still face some challenges in practical applications, such as insufficient capacity, insufficient thermal stability, insufficient interface stability, and insufficient structural stability.

[0005] CN114314692A discloses a ternary positive electrode material precursor and preparation method, positive electrode material, positive electrode slurry, lithium-ion battery, positive electrode and electrical equipment. The ternary positive electrode material precursor includes a core layer, an intermediate layer and a shell layer, and the porosity of the core layer, the intermediate layer and the shell layer increases in sequence. Preparation method: Mix raw materials including a nickel source, a cobalt source, a manganese source, a precipitant and ammonia, and react by a solution co-precipitation method. The positive electrode material, whose raw materials include the ternary positive electrode material precursor. The positive electrode slurry, whose raw materials include the positive electrode material. The lithium-ion battery positive electrode, whose raw materials include the lithium-ion battery positive electrode slurry. The lithium-ion battery, whose raw materials include the lithium-ion battery positive electrode. Electrical equipment, including lithium-ion batteries. However, the positive electrode material prepared from the ternary positive electrode material precursor has the problems of insufficient capacity, insufficient thermal stability and insufficient interface stability.

[0006] CN103500827A discloses a lithium-ion battery and its multi-element positive electrode material and preparation method. The chemical formula of the multi-element positive electrode material is Li x Ni a Co b Mn c N yO2, where N is the three elements Ti, Mg, and Al, 1.0 ≤ x ≤ 1.15, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0.003 ≤ y ≤ 0.07, and a + b + c + y = 1. Its layered structure includes: a core pure phase layer containing lithium nickel cobalt manganese oxide; a surface doping layer containing the doping element Ti; an oxide surface coating layer containing the coating element Al; and a superficial doping transition layer containing the doping element Mg located between the surface doping layer and the surface coating layer. The preparation method of the multi-component cathode material is as follows: First, synthesize a multi-component precursor containing nickel, cobalt, and manganese three elements in the bulk phase, then perform surface doping of Ti and lithiation treatment on the precursor liquid phase, and finally perform surface pyrometallurgical doping of Mg and coating of Al2O3 treatment to obtain a composite-modified multi-component lithium-ion cathode material. However, this multi-component cathode material has problems of insufficient capacity and insufficient interfacial stability.

[0007] The ternary precursors disclosed in the prior art all have certain defects, and there are problems of insufficient capacity, insufficient thermal stability, insufficient interfacial stability, and insufficient structural stability of the cathode materials prepared from the ternary precursors. Therefore, it is crucial to develop and design a new type of ternary precursor and its preparation method, cathode material and its preparation process, and battery. Summary of the Invention

[0008] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a ternary precursor and its preparation method, a cathode material and its preparation process, and a battery. The core of the ternary precursor provided by the present invention has the highest nickel content, which ensures the capacity of the cathode material prepared from the ternary precursor; the nickel content gradient changes in the core, transition layer, and outer shell, which improves the thermal stability of the ternary precursor; the outer shell reduces the interfacial side reactions between the cathode material prepared from the ternary precursor and the electrolyte; the transition layer can not only act as a buffer layer between the core and the outer shell, thereby improving the structural stability of the ternary precursor. Therefore, the battery containing the cathode material prepared from the ternary precursor has excellent capacity and cycle stability at both room temperature and high temperature.

[0009] To achieve this purpose, the present invention adopts the following technical solutions:

[0010] In the first aspect, the present invention provides a ternary precursor, which includes a core, and a transition layer and an outer shell sequentially coated outside the core;

[0011] [[ID=@17]]The nickel content of the core > the nickel content of the transition layer > the nickel content of the outer shell.

[0012] The core of the ternary precursor provided by the present invention has the highest nickel content. The core is a high-nickel ternary precursor, which ensures the capacity of the cathode material prepared from the ternary precursor, so that the prepared cathode material can meet the requirements of high capacity.

[0013] The shell of the ternary precursor provided by the present invention has the lowest nickel content and correspondingly higher cobalt and manganese contents. The shell with high cobalt and manganese content has stronger thermal stability, thereby improving the thermal stability of the ternary precursor and the positive electrode material prepared using the ternary precursor; in addition, the shell in the ternary precursor can also prevent the core with the highest nickel content from direct contact with the electrolyte, thereby reducing the interfacial side reactions between the positive electrode material prepared using the ternary precursor and the electrolyte.

[0014] In the ternary precursor provided by the present invention, a transition layer is introduced between the core and the shell. The transition layer can not only serve as a buffer layer between the core and the shell, thereby absorbing the stress between the core and the shell; it can also make the nickel content between the core, the transition layer and the shell change gradually, reduce lattice mutation, and inhibit crack propagation, thereby improving the structural stability of the ternary precursor and the positive electrode material prepared with the ternary precursor.

[0015] Therefore, the battery containing the positive electrode material prepared using the ternary precursor has excellent capacity and cycle stability at both room temperature and high temperature.

[0016] Preferably, the molar fraction of nickel in the core is 85-95% based on the total molar amount of metal elements in the core.

[0017] The molar fraction of nickel in the transition layer is 64.5-85% based on the total molar amount of the metal elements in the transition layer.

[0018] Based on the total molar amount of the metal elements in the shell as 100%, the molar fraction of nickel in the shell is 45-65%.

[0019] In the present invention, the molar fraction of nickel in the core is 85-95%, based on the total molar amount of the metal elements in the core. For example, it can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0020] In the present invention, based on the total molar amount of metal elements in the transition layer, the molar fraction of nickel in the transition layer is 64.5% to 85%, for example, it can be 64.5%, 65%, 68%, 71%, 74%, 77%, 80%, 83% or 85%, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0021] In the present invention, based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 45-65%, for example, it can be 45%, 48%, 51%, 54%, 57%, 60%, 63% or 65%, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0022] Preferably, the manganese content of the inner core is less than the manganese content of the transition layer and is less than the manganese content of the outer shell.

[0023] In the ternary precursor provided by the present invention, the outer shell has the highest manganese content, and the outer shell with a high manganese content has higher thermal stability, thereby further improving the thermal stability of the ternary precursor and the positive electrode material prepared using the ternary precursor; in addition, the manganese content in the transition layer is between the inner core and the outer shell, so that the manganese content of the inner core, the transition layer and the outer shell presents a gradient change, thereby further reducing the lattice mutation, inhibiting the expansion of cracks, and improving the structural stability of the ternary precursor and the positive electrode material prepared using the ternary precursor.

[0024] Preferably, the molar fraction of manganese in the core is 2.5 to 7.5%, based on the total molar amount of metal elements in the core.

[0025] The molar fraction of manganese in the transition layer is 7.5 to 22.5% based on the total molar amount of the metal elements in the transition layer.

[0026] Based on the total molar amount of the metal elements in the shell, the molar fraction of manganese in the shell is 17.5-30%.

[0027] In the present invention, the molar fraction of manganese in the core is 2.5-7.5%, based on the total molar amount of metal elements in the core. For example, it can be 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0% or 7.5%, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0028] In the present invention, based on the total molar amount of metal elements in the transition layer, the molar fraction of manganese in the transition layer is 7.5-22.5%, for example, it can be 7.5%, 9.0%, 10.5%, 12.0%, 13.5%, 15.0%, 16.5%, 18.0%, 19.5%, 21.0% or 22.5%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] In the present invention, the molar fraction of manganese in the shell is 17.5% to 30%, based on the total molar amount of the metal elements in the shell. For example, it can be 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%, 25.0%, 25.5%, 26.0%, 26.5%, 27.0%, 27.5%, 28.0%, 28.5%, 29.0%, 29.5% or 30.0%, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0030] Preferably, the transition layer also includes magnesium.

[0031] In the ternary precursor provided by the present invention, by doping the Mg element in the transition layer, the interfacial impedance of the positive electrode material prepared using the ternary precursor is further reduced, thereby enhancing the transmission efficiency of lithium ions; in addition, doping the Mg element in the transition layer can also reduce the mixing of lithium and nickel cations and enhance the structural stability of the ternary precursor.

[0032] Preferably, based on the total molar amount of metal elements in the transition layer, the molar fraction of magnesium in the transition layer is 0.1-0.3%, for example, it can be 0.10%, 0.12%, 0.14%, 0.16%, 0.18%, 0.20%, 0.22%, 0.24%, 0.26%, 0.28% or 0.30%, but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0033] In the present invention, the molar fraction of magnesium, calculated as a percentage of the total molar amount of metal elements in the transition layer, affects the performance of the ternary precursor, the positive electrode material, and the battery. When the molar fraction of magnesium is 0.1-0.3%, the battery exhibits better performance. This is because an appropriate amount of magnesium doping can optimize the electronic conductivity of the transition layer and relieve lattice stress, while maintaining structural stability while avoiding phase separation or ion transport blockage caused by excessive doping. This molar fraction range can effectively inhibit the mixing of nickel and lithium cations and reduce interfacial impedance, and can buffer the volume deformation during the cycle through the "pinning effect" of magnesium ions, thereby synergistically improving the capacity and cycle stability of the positive electrode material.

[0034] Preferably, the D50 particle size of the core is 8 to 10 μm, for example, it can be 8.0 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm or 10.0 μm, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0035] In the present invention, the D50 particle size of the core affects the performance of the ternary precursor, the positive electrode material and the battery; when the D50 particle size of the core is 8 to 10 μm, the battery exhibits better performance. The moderate core size can not only improve the tap density through dense stacking, but also alleviate the volume deformation difference between the core and the shell during charging and discharging, inhibit the generation of cracks, thereby synergistically improving the material capacity retention rate and rate performance, while providing basic support for the integrity of the gradient structure.

[0036] Preferably, the thickness of the transition layer is 0.5 to 3 μm, for example, it can be 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm or 3.0 μm, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0037] In the present invention, the thickness of the transition layer affects the performance of the ternary precursor, the positive electrode material and the battery; when the thickness of the transition layer is 0.5 to 3 μm, the battery exhibits better performance. This is because this thickness range can not only ensure the continuity of the gradient change of the manganese content to alleviate the lattice mismatch and stress concentration between the core and the shell, but also avoid insufficient stress buffering caused by too thin or long-range lithium ion diffusion resistance caused by too thick; the moderate thickness enables the transition layer to effectively inhibit volume deformation transmission, optimize the uniformity of magnesium doping, and maintain high electron / ion transmission efficiency, thereby synergistically improving the cycle stability, rate performance and high-temperature stability of the positive electrode material.

[0038] Preferably, the thickness of the shell is 0.5 to 4.5 μm, for example, it can be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm or 4.5 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In the present invention, the thickness of the shell affects the performance of the ternary precursor, the positive electrode material and the battery; when the thickness of the shell is 0.5 to 4.5 μm, the battery exhibits better performance. This is because this thickness range can effectively suppress the structural collapse caused by thermal runaway through the high manganese shell, and avoid insufficient mechanical strength caused by too thin or poor lithium ion diffusion kinetics caused by too thick.

[0040] Preferably, the D50 particle size of the ternary precursor is 11 to 13 μm, for example, it can be 11.0 μm, 11.2 μm, 11.4 μm, 11.6 μm, 11.8 μm, 12.0 μm, 12.2 μm, 12.4 μm, 12.6 μm, 12.8 μm or 13.0 μm, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0041] By limiting the particle sizes of the core, transition layer and shell in the present invention, it is possible to ensure that the positive electrode material prepared with the ternary precursor has a high capacity while ensuring that the positive electrode material has good thermal stability and fully reducing the risk of crack propagation in the positive electrode material.

[0042] In a second aspect, the present invention provides a method for preparing the ternary precursor according to the first aspect, the preparation method comprising:

[0043] (1) adding a first metal mixed salt solution, a precipitant solution, and an ammonia solution to a reaction bottom solution in parallel to perform a coprecipitation reaction to obtain a solution containing a core;

[0044] (2) adding the second metal mixed salt solution, the precipitant solution and the ammonia solution in parallel to the solution containing the core obtained in step (1) to perform a coprecipitation reaction to obtain a solution containing a precipitate;

[0045] (3) adding the third metal mixed salt solution, the precipitant solution and the ammonia solution in parallel to the solution containing the precipitate obtained in step (2) to perform a co-precipitation reaction to obtain a ternary precursor;

[0046] The nickel ion concentration in the first metal mixed salt solution in step (1) is greater than the nickel ion concentration in the second metal mixed salt solution in step (2) and is greater than the nickel ion concentration in the third metal mixed salt solution in step (3).

[0047] The present invention adopts a co-precipitation process to precisely control the formation of the core-shell structure by changing the reaction pH and the ratio of the metal salt solution.

[0048] Preferably, the manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0049] Preferably, in step (1), the first metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (85-95):(2.5-7.5):(2.5-7.5).

[0050] The first metal mixed salt solution in step (1) of the present invention contains nickel ions and cobalt ions in a molar ratio of (85-95): (2.5-7.5), for example, 85:2.5, 86:3.0, 87:3.5, 88:4.0, 89:4.5, 90:5.0, 91:5.5, 92:6.0, 93:6.5, 94:7.0 or 95:7.5, but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0051] The first metal mixed salt solution in step (1) of the present invention contains cobalt ions and manganese ions in a molar ratio of (2.5 to 7.5): (2.5 to 7.5), for example, 2.5:2.5, 3.0:3.0, 3.5:3.5, 4.0:4.0, 4.5:4.5, 5.0:5.0, 5.5:5.5, 6.0:6.0, 6.5:6.5, 7.0:7.0 or 7.5:7.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0052] Preferably, the total concentration of metal ions in the first metal mixed salt solution in step (1) is 1.0 to 2.5 mol / L, for example, it can be 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L or 2.5 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0053] Preferably, the second metal mixed salt solution in step (2) contains nickel ions, cobalt ions and manganese ions in a molar ratio of (65-85):(7.5-22.5):(7.5-22.5).

[0054] The second metal mixed salt solution in step (2) of the present invention contains nickel ions and cobalt ions in a molar ratio of (65-85):(7.5-22.5), for example, it can be 65:7.5, 68:9.0, 71:10.5, 74:12.0, 77:13.5, 80:15.0, 83:16.5, 85:18.0, 85:19.5, 85:21.0 or 85:22.5, but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0055] The second metal mixed salt solution in step (2) of the present invention contains cobalt ions and manganese ions in a molar ratio of (7.5 to 22.5): (7.5 to 22.5), for example, 7.5:7.5, 9.0:9.0, 10.5:10.5, 12.0:12.0, 13.5:13.5, 15.0:15.0, 16.5:16.5, 18.0:18.0, 19.5:19.5, 21.0:21.0 or 22.5:22.5, but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0056] Preferably, the second metal mixed salt solution in step (2) further includes magnesium ions.

[0057] In the step (2) of the present invention, the second metal mixed salt solution also includes magnesium ions. The wet doping method is used to introduce the doping element during the coprecipitation process, which can make the doping element Mg more evenly distributed, so that the Mg element can fully play its role in reducing the mixing of lithium and nickel cations and enhancing the stability of the crystal structure.

[0058] Preferably, in step (2), the total concentration of nickel ions, cobalt ions and manganese ions in the second metal mixed salt solution has a molar ratio to magnesium ions of 100:(0.1-0.3), for example, 100:0.1, 100:0.15, 100:0.2, 100:0.25 or 100:0.3, but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0059] Preferably, the total concentration of metal ions in the second metal mixed salt solution in step (2) is 1.0 to 2.5 mol / L, for example, it can be 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L or 2.5 mol / L, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0060] Preferably, the third metal mixed salt solution in step (3) contains nickel ions, cobalt ions and manganese ions in a molar ratio of (45-65):(17.5-25):(17.5-30).

[0061] The third metal mixed salt solution in step (3) of the present invention contains nickel ions and cobalt ions in a molar ratio of (45 to 65): (17.5 to 25), for example, 45:17.5, 47:18.0, 49:18.5, 51:19.0, 53:19.5, 55:20.0, 57:20.5, 59:21.0, 61:21.5, 63:22.0, 65:22.5, 65:23.0, 65:23.5, 65:24.0 or 65:25.0, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0062] The third metal mixed salt solution in step (3) of the present invention contains cobalt ions and manganese ions in a molar ratio of (17.5-25): (17.5-30), for example, 17.5:17.5, 18.0:18.0, 18.5:18.5, 19.0:19.0, 19.5:19.5, 20.0:20.0, 20.5:20.5, 21.0:21.0, 21.5:21.5, 22.0:22.0, 22.5:22.5, 23.0:2 3.0, 23.5:23.5, 24.0:24.0, 24.5:24.5, 25.0:25.0, 25.0:25.5, 25.0:26.0, 25.0:26.5, 25.0:27.0, 25.0:27.5, 25.0:28.0, 25.0:28.5, 25.0:29.0, 25.0:29.5 or 25.0:30.0, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0063] Preferably, the total concentration of metal ions in the third metal mixed salt solution in step (3) is 1.0 to 2.5 mol / L, for example, it can be 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L or 2.5 mol / L, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0064] Preferably, the salts in the first metal mixed salt solution in step (1), the second metal mixed salt solution in step (2), and the third metal mixed salt solution in step (3) each independently include sulfate.

[0065] Preferably, the pH of the reaction base solution in step (1) is 11.2-12, and the ammonia concentration is 4-12 g / L.

[0066] The pH of the reaction base solution in step (1) of the present invention is 11.2 to 12, for example, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9 or 12.0, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0067] The concentration of the reaction base solution in step (1) of the present invention is 4 to 12 g / L, for example, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L or 12 g / L, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0068] Preferably, the mass concentration of the precipitant in the precipitant solution in steps (1) to (3) is 20 to 40 wt%, for example, it can be 20 wt%, 22 wt%, 24 wt%, 26 wt%, 28 wt%, 30 wt%, 32 wt%, 34 wt%, 36 wt%, 38 wt% or 40 wt%, but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0069] Preferably, the precipitant in the precipitant solution in steps (1) to (3) independently comprises any one of sodium hydroxide, potassium hydroxide, sodium carbonate or ammonium carbonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium hydroxide and potassium hydroxide, a combination of sodium carbonate and ammonium carbonate, a combination of sodium hydroxide, potassium hydroxide and sodium carbonate, or a combination of potassium hydroxide, sodium carbonate and ammonium carbonate.

[0070] Preferably, the solvent in the precipitant solution in steps (1) to (3) independently comprises water.

[0071] Preferably, the mass concentration of ammonia in the ammonia solution in steps (1) to (3) is 10 to 30 wt%, for example, it can be 10 wt%, 12 wt%, 14 wt%, 16 wt%, 18 wt%, 20 wt%, 22 wt%, 24 wt%, 26 wt%, 28 wt% or 30 wt%, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0072] Preferably, the ammonia in the ammonia solution in steps (1) to (3) independently includes any one of ammonia, ethylenediaminetetraacetic acid, citric acid or oxalic acid, or a combination of at least two of them. Typical but non-limiting combinations include a combination of ammonia and ethylenediaminetetraacetic acid, a combination of citric acid and oxalic acid, a combination of ammonia, ethylenediaminetetraacetic acid and citric acid, or a combination of ethylenediaminetetraacetic acid, citric acid and oxalic acid.

[0073] Preferably, the solvent in the ammonia solution in steps (1) to (3) independently includes water.

[0074] Preferably, the temperature of the coprecipitation reaction in steps (1) to (3) is independently 40 to 80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0075] Preferably, the pH value of the coprecipitation reaction in steps (1) to (3) is independently 10 to 11, for example, it can be 10.0, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9 or 11.0, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0076] Preferably, the ammonia concentration of the coprecipitation reaction in steps (1) to (3) is independently 4 to 10 g / L, for example, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0077] Preferably, the addition flow rates of the first metal mixed salt solution added in parallel in step (1), the second metal mixed salt solution in step (2) and the third metal mixed salt solution in step (3) are independently 10 to 80 L / h, for example, 10 L / h, 20 L / h, 30 L / h, 40 L / h, 50 L / h, 60 L / h, 70 L / h or 80 L / h, but are not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0078] Preferably, the addition flow rate of the precipitant solution in the parallel addition in steps (1) to (3) is independently 2 to 20 L / h, for example, it can be 2 L / h, 4 L / h, 6 L / h, 8 L / h, 10 L / h, 12 L / h, 14 L / h, 16 L / h, 18 L / h or 20 L / h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0079] Preferably, the addition flow rate of the ammonia solution added in parallel in steps (1) to (3) is independently 2 to 10 L / h, for example, it can be 2 L / h, 3 L / h, 4 L / h, 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h or 10 L / h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] Preferably, steps (1) to (3) are all carried out in a protective atmosphere.

[0081] Preferably, the coprecipitation reaction in step (3) further comprises filtering, washing and drying in sequence.

[0082] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:

[0083] (1) In a protective atmosphere, a first metal mixed salt solution, a precipitant solution with a mass concentration of 20 to 40 wt%, and an ammonia solution with a mass concentration of 10 to 30 wt% are added concurrently to a reaction base solution with a pH of 11.2 to 12 and an ammonia concentration of 4 to 12 g / L, and the temperature is controlled at 40 to 80° C., the pH is 10 to 11, and the ammonia concentration is 4 to 10 g / L to perform a coprecipitation reaction to obtain a solution containing a core;

[0084] The first metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (85-95):(2.5-7.5):(2.5-7.5), and the total concentration of the metal ions is 1.0-2.5 mol / L;

[0085] (2) in a protective atmosphere, adding a second metal mixed salt solution, a precipitant solution having a mass concentration of 20 to 40 wt %, and an ammonia solution having a mass concentration of 10 to 30 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 40 to 80° C., the pH to 10 to 11, and the ammonia concentration to 4 to 10 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate;

[0086] The second metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (65-85):(7.5-22.5):(7.5-22.5);

[0087] The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:(0.1-0.3) to magnesium ions;

[0088] The total concentration of metal ions in the second metal mixed salt solution is 1.0 to 2.5 mol / L;

[0089] (3) in a protective atmosphere, adding a third metal mixed salt solution, a precipitant solution with a mass concentration of 20 to 40 wt%, and an ammonia solution with a mass concentration of 10 to 30 wt% to the solution containing the precipitate obtained in step (2) in parallel, controlling the temperature to 40 to 80° C., the pH to 10 to 11, and the ammonia concentration to 4 to 10 g / L, to carry out a coprecipitation reaction to obtain a ternary precursor;

[0090] The third metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (45-65):(17.5-25):(17.5-30), and the total concentration of the metal ions is 1.0-2.5 mol / L;

[0091] The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3);

[0092] The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0093] In a third aspect, the present invention provides a positive electrode material, which is prepared from the ternary precursor described in the first aspect.

[0094] In a fourth aspect, the present invention provides a process for preparing the positive electrode material according to the third aspect, the process comprising:

[0095] After mixing the lithium source and the ternary precursor described in the first aspect, heat treatment is performed in an oxygen-containing atmosphere to obtain the positive electrode material.

[0096] Preferably, the oxygen concentration in the oxygen-containing atmosphere is not less than 18%, for example, it can be 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 35%, 4%, 50%, 60% or 70%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] Preferably, the oxygen-containing atmosphere comprises an air atmosphere.

[0098] Preferably, the heat treatment temperature is 500-800° C., and the time is 6-10 hours.

[0099] The heat treatment temperature in the present invention is 500-800°C, for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values. Other unlisted values ​​within this numerical range are also applicable.

[0100] The heat treatment time in the present invention is 6 to 10 hours, for example, it can be 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours or 10 hours, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0101] In a fifth aspect, the present invention provides a battery comprising the positive electrode material described in the third aspect.

[0102] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0103] Compared with the prior art, the present invention has the following beneficial effects:

[0104] (1) The core of the ternary precursor provided by the present invention has the highest nickel content. The core is a high-nickel ternary precursor, which ensures the capacity of the positive electrode material prepared from the ternary precursor, so that the prepared positive electrode material can meet the demand for high capacity;

[0105] (2) The shell of the ternary precursor provided by the present invention has the lowest nickel content, and correspondingly has higher cobalt and manganese contents. The shell with high cobalt and manganese content has stronger thermal stability, thereby improving the thermal stability of the ternary precursor and the positive electrode material prepared with the ternary precursor; in addition, the shell of the ternary precursor can also prevent the core with the highest nickel content from directly contacting the electrolyte, thereby reducing the interfacial side reactions between the positive electrode material prepared with the ternary precursor and the electrolyte;

[0106] (3) In the ternary precursor provided by the present invention, a transition layer is introduced between the core and the shell. The transition layer can not only serve as a buffer layer between the core and the shell, thereby absorbing the stress between the core and the shell; it can also make the nickel content between the core, the transition layer and the shell change gradually, reduce the lattice mutation, and inhibit the crack propagation, thereby improving the structural stability of the ternary precursor and the positive electrode material prepared by the ternary precursor;

[0107] (4) Batteries containing cathode materials prepared using ternary precursors have excellent capacity and cycle stability at both room and high temperatures. DETAILED DESCRIPTION

[0108] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0109] Example 1

[0110] This embodiment provides a ternary precursor, comprising a core with a D50 particle size of 10 μm, and a transition layer with a thickness of 1 μm and a shell with a thickness of 1 μm sequentially coated on the outside of the core, and the D50 particle size of the ternary precursor is 12 μm;

[0111] The nickel content of the core>the nickel content of the transition layer>the nickel content of the shell;

[0112] The manganese content of the inner core is less than the manganese content of the transition layer and less than the manganese content of the outer shell;

[0113] The transition layer also includes magnesium;

[0114] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 92%, the molar fraction of cobalt is 4%, and the molar fraction of manganese is 4%.

[0115] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 69.86%, the molar fraction of cobalt is 19.96%, the molar fraction of manganese is 9.98%, and the molar fraction of magnesium is 0.20%.

[0116] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 50%, the molar fraction of cobalt is 20%, and the molar fraction of manganese is 30%;

[0117] The preparation method of the ternary precursor comprises:

[0118] (1) In a protective atmosphere, a first metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 30 wt %, and ammonia water with a mass concentration of 20 wt % are added concurrently to a reaction base solution with a pH of 11.5 and an ammonia concentration of 8 g / L, and the temperature is controlled to be 60° C., the pH value is 10.5, and the ammonia concentration is 8 g / L to perform a coprecipitation reaction to obtain a solution containing a core;

[0119] The first metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 92:4:4, and the total concentration of the metal ions is 2 mol / L;

[0120] (2) in a protective atmosphere, adding a second metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 30 wt %, and ammonia water with a mass concentration of 20 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 60° C., the pH to 10.5, and the ammonia concentration to 8 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate;

[0121] The second metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of 70:10:20;

[0122] The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:0.2 to magnesium ions;

[0123] The total concentration of metal ions in the second metal mixed salt solution is 2 mol / L;

[0124] (3) In a protective atmosphere, a third metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 30 wt %, and an ammonia solution with a mass concentration of 20 wt % are added to the solution containing the precipitate obtained in step (2) in parallel, and the temperature is controlled to be 60° C., the pH value is 10.5, and the ammonia concentration is 8 g / L to perform a coprecipitation reaction to obtain a ternary precursor;

[0125] The third metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 50:20:30, and the total concentration of the metal ions is 2 mol / L;

[0126] The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3);

[0127] The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0128] Example 2

[0129] This embodiment provides a ternary precursor, comprising a core with a D50 particle size of 9 μm, and a transition layer with a thickness of 0.5 μm and a shell with a thickness of 1.5 μm sequentially coated on the outside of the core, and the D50 particle size of the ternary precursor is 11 μm;

[0130] The nickel content of the core>the nickel content of the transition layer>the nickel content of the shell;

[0131] The manganese content of the inner core is less than the manganese content of the transition layer and less than the manganese content of the outer shell;

[0132] The transition layer also includes magnesium;

[0133] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 92%, the molar fraction of cobalt is 5%, and the molar fraction of manganese is 3%;

[0134] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 79.84%, the molar fraction of cobalt is 9.98%, the molar fraction of manganese is 9.98%, and the molar fraction of magnesium is 0.20%.

[0135] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 60%, the molar fraction of cobalt is 20%, and the molar fraction of manganese is 20%;

[0136] The preparation method of the ternary precursor comprises:

[0137] (1) In a protective atmosphere, a first metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 32 wt %, and ammonia water with a mass concentration of 22 wt % are added concurrently to a reaction base solution with a pH of 11.5 and an ammonia concentration of 8 g / L, and the temperature is controlled to be 60° C., the pH value is 10.6, and the ammonia concentration is 8 g / L to perform a coprecipitation reaction to obtain a solution containing a core;

[0138] The first metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 92:5:3, and the total concentration of the metal ions is 2.5 mol / L;

[0139] (2) in a protective atmosphere, adding a second metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 32 wt %, and ammonia water with a mass concentration of 22 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 60° C., the pH to 10.6, and the ammonia concentration to 8 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate;

[0140] The second metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of 80:10:10;

[0141] The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:0.2 to magnesium ions;

[0142] The total concentration of metal ions in the second metal mixed salt solution is 2.5 mol / L;

[0143] (3) In a protective atmosphere, a third metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 32 wt %, and an ammonia solution with a mass concentration of 22 wt % are added in parallel to the solution containing the precipitate obtained in step (2), and the temperature is controlled to be 60° C., the pH value is 10.6, and the ammonia concentration is 8 g / L to perform a coprecipitation reaction to obtain a ternary precursor;

[0144] The third metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 60:20:20, and the total concentration of the metal ions is 2.5 mol / L;

[0145] The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3);

[0146] The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0147] Example 3

[0148] This embodiment provides a ternary precursor, comprising a core with a D50 particle size of 9 μm, and a transition layer with a thickness of 1.8 μm and a shell with a thickness of 2.2 μm sequentially coated on the outside of the core, and the D50 particle size of the ternary precursor is 13 μm;

[0149] The nickel content of the core>the nickel content of the transition layer>the nickel content of the shell;

[0150] The manganese content of the inner core is less than the manganese content of the transition layer and less than the manganese content of the outer shell;

[0151] The transition layer also includes magnesium;

[0152] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 90%, the molar fraction of cobalt is 5%, and the molar fraction of manganese is 5%;

[0153] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 79.84%, the molar fraction of cobalt is 9.98%, the molar fraction of manganese is 9.98%, and the molar fraction of magnesium is 0.20%.

[0154] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 60%, the molar fraction of cobalt is 20%, and the molar fraction of manganese is 20%;

[0155] The preparation method of the ternary precursor comprises:

[0156] (1) In a protective atmosphere, a first metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 30 wt %, and an ammonia solution with a mass concentration of 20 wt % are added concurrently to a reaction base solution with a pH of 11.6 and an ammonia concentration of 8 g / L, and the temperature is controlled to be 60° C., the pH value is 10.5, and the ammonia concentration is 7 g / L to perform a coprecipitation reaction to obtain a solution containing a core;

[0157] The first metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 90:5:5, and the total concentration of the metal ions is 1.8 mol / L;

[0158] (2) in a protective atmosphere, adding a second metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 30 wt %, and ammonia water with a mass concentration of 20 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 60° C., the pH to 10.5, and the ammonia concentration to 7 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate;

[0159] The second metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of 80:10:10;

[0160] The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:0.2 to magnesium ions;

[0161] The total concentration of metal ions in the second metal mixed salt solution is 1.8 mol / L;

[0162] (3) In a protective atmosphere, a third metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 30 wt %, and an ammonia solution with a mass concentration of 20 wt % are added to the solution containing the precipitate obtained in step (2) in parallel, and the temperature is controlled to be 60° C., the pH value is 10.5, and the ammonia concentration is 7 g / L to perform a coprecipitation reaction to obtain a ternary precursor;

[0163] The third metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 60:20:20, and the total concentration of the metal ions is 1.8 mol / L;

[0164] The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3);

[0165] The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0166] Example 4

[0167] This embodiment provides a ternary precursor, comprising a core with a D50 particle size of 8 μm, and a transition layer with a thickness of 0.5 μm and a shell with a thickness of 4.5 μm sequentially coated on the outside of the core, and the D50 particle size of the ternary precursor is 13 μm;

[0168] The nickel content of the core>the nickel content of the transition layer>the nickel content of the shell;

[0169] The manganese content of the inner core is less than the manganese content of the transition layer and less than the manganese content of the outer shell;

[0170] The transition layer also includes magnesium;

[0171] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 95%, the molar fraction of cobalt is 2.5%, and the molar fraction of manganese is 2.5%;

[0172] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 64.80%, the molar fraction of cobalt is 17.45%, the molar fraction of manganese is 17.45%, and the molar fraction of magnesium is 0.30%.

[0173] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 45%, the molar fraction of cobalt is 25%, and the molar fraction of manganese is 30%;

[0174] The preparation method of the ternary precursor comprises:

[0175] (1) In a protective atmosphere, a first metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 20 wt %, and ammonia water with a mass concentration of 10 wt % are added concurrently to a reaction base solution with a pH of 11.2 and an ammonia concentration of 4 g / L, and the temperature is controlled to be 80° C., the pH value is 10, and the ammonia concentration is 4 g / L to perform a coprecipitation reaction to obtain a solution containing a core;

[0176] The first metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 95:2.5:2.5, and the total concentration of the metal ions is 2.5 mol / L;

[0177] (2) in a protective atmosphere, adding a second metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 20 wt %, and ammonia water with a mass concentration of 10 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 80° C., the pH to 10, and the ammonia concentration to 4 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate;

[0178] The second metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 65:17.5:17.5;

[0179] The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:0.3 to magnesium ions;

[0180] The total concentration of metal ions in the second metal mixed salt solution is 2.5 mol / L;

[0181] (3) In a protective atmosphere, a third metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 20 wt %, and an ammonia solution with a mass concentration of 10 wt % are added in parallel to the solution containing the precipitate obtained in step (2), and the temperature is controlled to be 80° C., the pH value is 10, and the ammonia concentration is 4 g / L to perform a coprecipitation reaction to obtain a ternary precursor;

[0182] The third metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 45:25:30, and the total concentration of the metal ions is 2.5 mol / L;

[0183] The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3);

[0184] The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0185] Example 5

[0186] This embodiment provides a ternary precursor, comprising a core with a D50 particle size of 9 μm, and a transition layer with a thickness of 3 μm and a shell with a thickness of 0.5 μm sequentially coated on the outside of the core, and the D50 particle size of the ternary precursor is 12.5 μm;

[0187] The nickel content of the core>the nickel content of the transition layer>the nickel content of the shell;

[0188] The manganese content of the inner core is less than the manganese content of the transition layer and less than the manganese content of the outer shell;

[0189] The transition layer also includes magnesium;

[0190] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 85%, the molar fraction of cobalt is 7.5%, and the molar fraction of manganese is 7.5%;

[0191] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 74.92%, the molar fraction of cobalt is 12.49%, the molar fraction of manganese is 12.49%, and the molar fraction of magnesium is 0.10%.

[0192] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 65%, the molar fraction of cobalt is 17.5%, and the molar fraction of manganese is 17.5%;

[0193] The preparation method of the ternary precursor comprises:

[0194] (1) In a protective atmosphere, a first metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 40 wt %, and an ammonia solution with a mass concentration of 30 wt % are added concurrently to a reaction base solution with a pH of 12 and an ammonia concentration of 12 g / L, and the temperature is controlled at 40° C., the pH is 11, and the ammonia concentration is 10 g / L to perform a coprecipitation reaction to obtain a solution containing a core;

[0195] The first metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 85:7.5:7.5, and the total concentration of the metal ions is 1.0 mol / L;

[0196] (2) in a protective atmosphere, adding a second metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 40 wt %, and ammonia water with a mass concentration of 30 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 40° C., the pH to 11, and the ammonia concentration to 10 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate;

[0197] The second metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 75:12.5:12.5;

[0198] The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:0.1 to magnesium ions;

[0199] The total concentration of metal ions in the second metal mixed salt solution is 1.0 mol / L;

[0200] (3) In a protective atmosphere, a third metal mixed salt solution, a sodium hydroxide solution with a mass concentration of 40 wt %, and an ammonia solution with a mass concentration of 30 wt % are added in parallel to the solution containing the precipitate obtained in step (2), and the temperature is controlled to be 40° C., the pH value is 11, and the ammonia concentration is 10 g / L to perform a coprecipitation reaction to obtain a ternary precursor;

[0201] The third metal mixed salt solution contains nickel ions, cobalt ions, and manganese ions in a molar ratio of 65:17.5:17.5, and the total concentration of the metal ions is 1.0 mol / L;

[0202] The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3);

[0203] The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

[0204] Example 6

[0205] This embodiment provides a ternary precursor, except that the manganese content of the core < the manganese content of the transition layer = the manganese content of the shell; that is:

[0206] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 74.92%, the molar fraction of cobalt is 9.98%, the molar fraction of manganese is 15.00%, and the molar fraction of magnesium is 0.10%.

[0207] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 65%, the molar fraction of cobalt is 20%, and the molar fraction of manganese is 15%, and the rest is the same as in Example 5.

[0208] Example 7

[0209] This embodiment provides a ternary precursor, except that the manganese content of the transition layer is greater than the manganese content of the outer shell and greater than the manganese content of the inner core, that is:

[0210] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 74.92%, the molar fraction of cobalt is 4.98%, the molar fraction of manganese is 20.00%, and the molar fraction of magnesium is 0.10%. Others are the same as those in Example 5.

[0211] Example 8

[0212] This embodiment provides a ternary precursor, which is the same as Example 5 except that the magnesium element in the transition layer is omitting, that is, based on the total molar amount of metal elements in the transition layer, the molar fraction of nickel in the transition layer is 75%, the molar fraction of cobalt is 12.5%, and the molar fraction of manganese is 12.5%.

[0213] Example 9

[0214] This embodiment provides a ternary precursor, which is the same as Example 5 except that the total molar amount of the metal elements in the transition layer is 100%, the molar fraction of nickel in the transition layer is 74.97%, the molar fraction of cobalt is 12.49%, the molar fraction of manganese is 12.49%, and the molar fraction of magnesium is 0.05%.

[0215] Example 10

[0216] This embodiment provides a ternary precursor, which is the same as Example 5 except that the total molar amount of the metal elements in the transition layer is 100%, the molar fraction of nickel in the transition layer is 74.62%, the molar fraction of cobalt is 12.44%, the molar fraction of manganese is 12.44%, and the molar fraction of magnesium is 0.50%.

[0217] Example 11

[0218] This embodiment provides a ternary precursor, which is the same as that of Example 5 except that the D50 particle size of the core is 7 μm and the D50 particle size of the ternary precursor is 10.5 μm.

[0219] Example 12

[0220] This embodiment provides a ternary precursor, which is the same as that of Example 5 except that the D50 particle size of the core is 12 μm and the D50 particle size of the ternary precursor is 15.5 μm.

[0221] Example 13

[0222] This embodiment provides a ternary precursor, which is the same as that of Example 5 except that the thickness of the transition layer is 0.2 μm and the D50 particle size of the ternary precursor is 9.7 μm.

[0223] Example 14

[0224] This embodiment provides a ternary precursor, which is the same as that of Example 5 except that the thickness of the transition layer is 4 μm and the D50 particle size of the ternary precursor is 13.5 μm.

[0225] Example 15

[0226] This embodiment provides a ternary precursor, which is the same as that of Example 5 except that the thickness of the shell is 0.2 μm and the D50 particle size of the ternary precursor is 12.3 μm.

[0227] Example 16

[0228] This embodiment provides a ternary precursor, which is the same as that of Example 5 except that the thickness of the shell is 5.5 μm and the D50 particle size of the ternary precursor is 17.5 μm.

[0229] Comparative Example 1

[0230] This comparative example provides a ternary precursor, except that the nickel content of the core is less than the nickel content of the transition layer and less than the nickel content of the shell, that is:

[0231] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 65%, the molar fraction of cobalt is 17.5%, and the molar fraction of manganese is 17.5%;

[0232] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 74.92%, the molar fraction of cobalt is 12.49%, the molar fraction of manganese is 12.49%, and the molar fraction of magnesium is 0.10%.

[0233] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 85%, the molar fraction of cobalt is 7.5%, and the molar fraction of manganese is 7.5%. Others are the same as those in Example 5.

[0234] Comparative Example 2

[0235] This comparative example provides a ternary precursor, except that the nickel content of the transition layer is greater than the nickel content of the core and greater than the nickel content of the shell, that is:

[0236] Based on the total molar amount of the metal elements in the core, the molar fraction of nickel in the core is 75%, the molar fraction of cobalt is 12.5%, and the molar fraction of manganese is 12.5%;

[0237] Based on the total molar amount of the metal elements in the transition layer, the molar fraction of nickel in the transition layer is 84.92%, the molar fraction of cobalt is 7.49%, the molar fraction of manganese is 7.49%, and the molar fraction of magnesium is 0.10%.

[0238] Based on the total molar amount of the metal elements in the shell, the molar fraction of nickel in the shell is 65%, the molar fraction of cobalt is 17.5%, and the molar fraction of manganese is 17.5%. Others are the same as those in Example 5.

[0239] Comparative Example 3

[0240] This comparative example provides a ternary precursor, which is the same as Example 5 except that the transition layer is omitted and the D50 particle size of the core is increased to 12 μm to ensure that the particle size of the ternary precursor remains unchanged.

[0241] Comparative Example 4

[0242] This comparative example provides a ternary precursor, which is the same as Example 5 except that the transition layer is omitted and the thickness of the outer shell is increased to 3.5 μm to ensure that the particle size of the ternary precursor remains unchanged.

[0243] The ternary precursor provided in the above embodiments and comparative examples was mixed with lithium hydroxide in a ratio of 1:1.05, and sintered at 650°C for 8h to obtain a positive electrode material; the obtained positive electrode material was then mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 90:5:5, and N-methylpyrrolidone was used as the solvent, and the mixture was stirred into a slurry; the obtained slurry was evenly coated on an aluminum foil with a scraper with a coating gap of 100μm; after coating, it was first blown dry, then rolled and cut into circular electrode sheets, and then vacuum dried at 120°C and the weight of the electrode sheets was weighed to obtain a button half-cell positive electrode sheet; a metal lithium sheet was selected as the negative electrode, a PP microporous membrane was selected as the diaphragm, and a lithium battery basic electrolyte was selected as the electrolyte. The positive electrode sheet, the metal lithium sheet, the diaphragm and the electrolyte were assembled to obtain a button battery.

[0244] The electrochemical performance of the button cell was tested at 25°C, in the voltage range of 2.8 to 4.3 V, and at a rate of 0.1C. The initial discharge capacity of the button cell at 25°C and the capacity retention rate after 300 cycles are shown in Table 1.

[0245] The electrochemical performance of the button cell was tested at 45°C in the voltage range of 2.8 to 4.3 V and a rate of 0.1C. The initial discharge capacity of the button cell at 45°C and the capacity retention rate after 300 cycles are shown in Table 2.

[0246] Table 1

[0247]

[0248] Table 2

[0249]

[0250]

[0251] From Table 1 and Table 2, we can get:

[0252] (1) The cathode materials prepared using the ternary precursors provided in Examples 1 to 5 have more excellent performance. Batteries prepared using the obtained cathode materials exhibit higher initial discharge capacity and higher cycle stability at both 25°C and 45°C.

[0253] (2) By comparing Examples 5 with 6 and 7, it can be seen that in the ternary precursor provided by the present invention, the shell has the highest manganese content, and the shell with a high manganese content has a higher thermal stability, thereby further improving the thermal stability of the ternary precursor and the positive electrode material prepared with the ternary precursor; in addition, the manganese content in the transition layer is between the core and the shell, so that the manganese content of the core, the transition layer and the shell presents a gradient change, thereby further reducing the lattice mutation, inhibiting the expansion of cracks, and improving the structural stability of the ternary precursor and the positive electrode material prepared with the ternary precursor;

[0254] (3) By comparing Example 5 with Example 8, it can be seen that in the ternary precursor provided by the present invention, by doping the Mg element in the transition layer, the interfacial impedance of the positive electrode material prepared by the ternary precursor is further reduced, and the transmission efficiency of lithium ions is enhanced; in addition, doping the Mg element in the transition layer can also reduce the mixing of lithium and nickel cations and enhance the structural stability of the ternary precursor;

[0255] (4) By comparing Example 5 with Examples 9 and 10, it can be seen that in the present invention, the molar fraction of magnesium, based on the total molar amount of metal elements in the transition layer, will affect the performance of the ternary precursor, the positive electrode material and the battery; when the molar fraction of magnesium is 0.1-0.3%, the battery exhibits better performance, which is because an appropriate amount of magnesium doping can optimize the electronic conductivity of the transition layer and relieve lattice stress, while maintaining structural stability and avoiding phase separation or ion transport blockage caused by excessive doping; this molar fraction range can not only effectively inhibit the mixing of nickel and lithium cations and reduce interfacial impedance, but also buffer the volume deformation during the cycle through the "pinning effect" of magnesium ions, thereby synergistically improving the capacity and cycle stability of the positive electrode material;

[0256] (5) By comparing Example 5 with Examples 11 and 12, it can be seen that in the present invention, the D50 particle size of the core affects the performance of the ternary precursor, the positive electrode material and the battery; when the D50 particle size of the core is 8 to 10 μm, the battery exhibits better performance. The moderate core size can not only improve the tap density by dense stacking, but also alleviate the volume deformation difference between the core and the shell during charging and discharging, inhibit the generation of cracks, thereby synergistically improving the material capacity retention rate and rate performance, and at the same time providing basic support for the integrity of the gradient structure;

[0257] (6) By comparing Example 5 with Examples 13 and 14, it can be seen that in the present invention, the thickness of the transition layer affects the performance of the ternary precursor, the positive electrode material and the battery; when the thickness of the transition layer is 0.5 to 3 μm, the battery shows better performance. This is because this thickness range can not only ensure the continuity of the gradient change of the manganese content to alleviate the lattice mismatch and stress concentration between the core and the shell, but also avoid insufficient stress buffering caused by too thin or long-range diffusion resistance of lithium ions caused by too thick; the moderate thickness enables the transition layer to effectively inhibit volume deformation transmission, optimize the uniformity of magnesium doping, and maintain high electron / ion transmission efficiency, thereby synergistically improving the cycle stability, rate performance and high-temperature stability of the positive electrode material;

[0258] (7) By comparing Example 5 with Examples 15 and 16, it can be seen that in the present invention, the thickness of the shell affects the performance of the ternary precursor, the positive electrode material and the battery; when the thickness of the shell is 0.5 to 4.5 μm, the battery shows better performance. This is because this thickness range can effectively suppress the structural collapse caused by thermal runaway through the high manganese shell, and can avoid the mechanical strength deficiency caused by too thin or the deterioration of lithium ion diffusion kinetics caused by too thick;

[0259] (8) By comparing Example 5 with Comparative Examples 1 to 4, it can be seen that the core of the ternary precursor provided by the present invention has the highest nickel content. The core is a high-nickel ternary precursor, which ensures the capacity of the positive electrode material prepared by the ternary precursor, so that the prepared positive electrode material can meet the high capacity requirement;

[0260] The shell of the ternary precursor provided by the present invention has the lowest nickel content and correspondingly higher cobalt and manganese contents. The shell with high cobalt and manganese content has stronger thermal stability, thereby improving the thermal stability of the ternary precursor and the positive electrode material prepared using the ternary precursor. In addition, the shell of the ternary precursor can also prevent direct contact between the core with the highest nickel content and the electrolyte, thereby reducing interfacial side reactions between the positive electrode material prepared using the ternary precursor and the electrolyte.

[0261] The ternary precursor provided by the present invention introduces a transition layer between the core and the shell. The transition layer not only serves as a buffer layer between the core and the shell, thereby absorbing the stress between the core and the shell; it also enables the nickel content between the core, the transition layer and the shell to change gradually, reducing lattice mutations and inhibiting crack propagation, thereby improving the structural stability of the ternary precursor and the positive electrode material prepared using the ternary precursor.

[0262] Therefore, the battery containing the positive electrode material prepared using the ternary precursor has excellent capacity and cycle stability at both room temperature and high temperature.

[0263] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.

Claims

1. A ternary precursor, characterized in that: The ternary precursor comprises a core, and a transition layer and a shell sequentially covering the outside of the core; The nickel content of the inner core is greater than the nickel content of the transition layer and greater than the nickel content of the outer shell.

2. The ternary precursor according to claim 1, characterized in that The molar fraction of nickel in the core is 85-95% based on the total molar amount of metal elements in the core; The molar fraction of nickel in the transition layer is 64.8-85% based on the total molar amount of the metal elements in the transition layer. The molar fraction of nickel in the shell is 45 to 65%, based on the total molar amount of the metal elements in the shell. Preferably, the manganese content of the inner core is less than the manganese content of the transition layer and is less than the manganese content of the outer shell; Preferably, the molar fraction of manganese in the core is 2.5 to 7.5%, based on the total molar amount of metal elements in the core. The molar fraction of manganese in the transition layer is 7.5 to 22.5% based on the total molar amount of the metal elements in the transition layer. The molar fraction of manganese in the shell is 17.5 to 30% based on the total molar amount of the metal elements in the shell; Preferably, the transition layer further includes magnesium; Preferably, based on the total molar amount of metal elements in the transition layer, the molar fraction of magnesium in the transition layer is 0.1-0.3%.

3. The ternary precursor according to claim 1, characterized in that The D50 particle size of the core is 8 to 10 μm; Preferably, the thickness of the transition layer is 0.5 to 3 μm; Preferably, the thickness of the shell is 0.5 to 4.5 μm; Preferably, the D50 particle size of the ternary precursor is 11-13 μm.

4. A method for preparing the ternary precursor according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) adding a first metal mixed salt solution, a precipitant solution, and an ammonia solution to a reaction bottom solution in parallel to perform a coprecipitation reaction to obtain a solution containing a core; (2) adding the second metal mixed salt solution, the precipitant solution and the ammonia solution in parallel to the solution containing the core obtained in step (1) to perform a coprecipitation reaction to obtain a solution containing a precipitate; (3) adding the third metal mixed salt solution, the precipitant solution and the ammonia solution in parallel to the solution containing the precipitate obtained in step (2) to perform a co-precipitation reaction to obtain a ternary precursor; The nickel ion concentration in the first metal mixed salt solution in step (1) is greater than the nickel ion concentration in the second metal mixed salt solution in step (2) and is greater than the nickel ion concentration in the third metal mixed salt solution in step (3).

5. The preparation method according to claim 4, characterized in that The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

6. The preparation method according to claim 4, characterized in that The second metal mixed salt solution in step (2) further includes magnesium ions; Preferably, the pH of the reaction base solution in step (1) is 11.2-12, and the ammonia concentration is 4-12 g / L; Preferably, the pH values ​​of the coprecipitation reactions in steps (1) to (3) are independently 10 to 11; Preferably, the ammonia concentration of the coprecipitation reaction in steps (1) to (3) is independently 4 to 10 g / L.

7. The preparation method according to claim 4, characterized in that The preparation method comprises: (1) In a protective atmosphere, a first metal mixed salt solution, a precipitant solution with a mass concentration of 20 to 40 wt%, and an ammonia solution with a mass concentration of 10 to 30 wt% are added concurrently to a reaction base solution with a pH of 11.2 to 12 and an ammonia concentration of 4 to 12 g / L, and the temperature is controlled at 40 to 80° C., the pH is 10 to 11, and the ammonia concentration is 4 to 10 g / L to perform a coprecipitation reaction to obtain a solution containing a core; The first metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (85-95):(2.5-7.5):(2.5-7.5), and the total concentration of the metal ions is 1.0-2.5 mol / L; (2) in a protective atmosphere, adding a second metal mixed salt solution, a precipitant solution having a mass concentration of 20 to 40 wt %, and an ammonia solution having a mass concentration of 10 to 30 wt % to the solution containing the core obtained in step (1) in parallel, controlling the temperature to 40 to 80° C., the pH to 10 to 11, and the ammonia concentration to 4 to 10 g / L, to carry out a coprecipitation reaction to obtain a solution containing a precipitate; The second metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (65-85):(7.5-22.5):(7.5-22.5); The second metal mixed salt solution also includes magnesium ions, and the total concentration of nickel ions, cobalt ions and manganese ions has a molar ratio of 100:(0.1-0.3) to magnesium ions; The total concentration of metal ions in the second metal mixed salt solution is 1.0 to 2.5 mol / L; (3) in a protective atmosphere, adding a third metal mixed salt solution, a precipitant solution with a mass concentration of 20 to 40 wt%, and an ammonia solution with a mass concentration of 10 to 30 wt% to the solution containing the precipitate obtained in step (2) in parallel, controlling the temperature to 40 to 80° C., the pH to 10 to 11, and the ammonia concentration to 4 to 10 g / L, to carry out a coprecipitation reaction to obtain a ternary precursor; The third metal mixed salt solution contains nickel ions, cobalt ions and manganese ions in a molar ratio of (45-65):(17.5-25):(17.5-30), and the total concentration of the metal ions is 1.0-2.5 mol / L; The nickel ion concentration in the first metal mixed salt solution in step (1)>the nickel ion concentration in the second metal mixed salt solution in step (2)>the nickel ion concentration in the third metal mixed salt solution in step (3); The manganese ion concentration in the first metal mixed salt solution in step (1) is less than the manganese ion concentration in the second metal mixed salt solution in step (2) and is less than the manganese ion concentration in the third metal mixed salt solution in step (3).

8. A positive electrode material, characterized in that The positive electrode material is prepared from the ternary precursor according to any one of claims 1 to 3.

9. A process for preparing the positive electrode material according to claim 8, characterized in that: The preparation process comprises: After mixing a lithium source with the ternary precursor according to any one of claims 1 to 4, heat treatment is performed in an oxygen-containing atmosphere to obtain the positive electrode material.

10. A battery, characterized in that: The battery comprises the positive electrode material according to claim 8.

Citation Information

Patent Citations

  • Lithium ion battery and multi-element positive material thereof as well as preparation method of multi-element positive material

    CN103500827A

Cited By

  • Ternary positive electrode material precursor, ternary positive electrode material, preparation method of ternary positive electrode material and lithium ion battery

    CN121054692A

  • A ternary positive electrode material precursor, a ternary positive electrode material, a preparation method thereof and a lithium ion battery

    CN121054692B

  • Metal hydroxide precursor particle and preparation method and application thereof

    CN121672605A

  • Positive electrode material precursor and preparation method and application thereof

    CN121929759A